Analyzing The FlySafe System Face to Malicious UAVs Playing Black Hole Attacks - Batista, Agnaldo; Santos, Aldri (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais do XXVI Simpósio Brasileiro de Cibersegurança, 2026)
Many of UAV networks demand dynamic structural topological services, such as sharing UAV location information, to provide UAV-coordinated and safe flight. More than just fault-tolerant, this basic service must be resilient to black hole attacks that aim corrupt and damage the UAV network topology by ignoring the neighborhood information. This work analyzes the resilience of the FlySafe system for protecting UAV networks against malicious UAV performing black hole attacks when they disregard sharing location information about its neighbors in a swarm environment. The FlySafe system relies on opportunistic approaches like epidemic and direct delivery, and enhancing neighbor discovery process. A simulation evaluation with NS3 showed the security of the location service, particularly in detecting and segregating black hole attacks from network operation with an average accuracy of 96%. Further, FlySafe exhibited an improvement in overall neighborhood perception in about 49.9%.